Indigenous Motherhood and Indian Hospitals: Exploring the Impact on Generational Indigenous Mothering Using Feminist Ethnography as a Decolonial Practice - Posca, Emma (Journal of the Motherhood Initiative for Research and Community Involvement, 2020)
Colonialism creates dehumanizing situations and alienates those who are colonized not only from themselves but also from their culture, language, and lands. Settler colonialism is defined as “settlement over Indigenous people and land” (Hart 25). Indigenous women in Canada were faced with colonizers who interfered with their matriarchy and egalitarian community values. Patriarchal views, which were at the core of colonialism, established controlling and eradication mechanisms in the form of “institutions such as Indian hospitals” (Brant 9). Both the physical and psychological abuse that was inflicted upon Indigenous women in Indian hospitals affected the mothering role and being mothered for both Indigenous women and children, which, ultimately, caused intergenerational trauma. Ethnographic storytelling and Indigenous feminism formulate a resistance as well as an activist stance towards colonial governments but also provide resources for a formal education for non-Indigenous people as part of a decolonial movement.